2012
DOI: 10.1186/1471-2458-12-618
|View full text |Cite
|
Sign up to set email alerts
|

Legionella on board trains: effectiveness of environmental surveillance and decontamination

Abstract: BackgroundLegionella pneumophila is increasingly recognised as a significant cause of sporadic and epidemic community-acquired and nosocomial pneumonia. Many studies describe the frequency and severity of Legionella spp. contamination in spa pools, natural pools, hotels and ships, but there is no study analysing the environmental monitoring of Legionella on board trains. The aims of the present study were to conduct periodic and precise environmental surveillance of Legionella spp. in water systems and water t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…may persist in hospital environment for several years, even at undetectable levels as Legionella Viable but non Culturable (VBNC), causing sporadic infections or epidemics [ 26 , 27 ]. Even if hyperchlorination of the water is consistently performed, this approach is particularly appropriate for the treatment and removal of planktonic cultures of legionella, but remains ineffective against sessile communities of the bacterium [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…may persist in hospital environment for several years, even at undetectable levels as Legionella Viable but non Culturable (VBNC), causing sporadic infections or epidemics [ 26 , 27 ]. Even if hyperchlorination of the water is consistently performed, this approach is particularly appropriate for the treatment and removal of planktonic cultures of legionella, but remains ineffective against sessile communities of the bacterium [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the time of our study, we found only one paper carried out on passenger trains, collecting water from plumbing and toilet water tanks before and after chlorine-based disinfection treatment [ 22 ]. Our monitoring results showed similar percentages of Legionella positivity, species, and serogroups as in pre-decontamination samples of Quaranta et al 2012 [ 22 ]; namely, they found more than 50% of water samples positive for Legionella , they identified only the L. pneumophila species, and the most frequently isolated was L. pneumophila sg1. Regarding the Legionella concentrations, our study found slightly higher values, but still with a geometric means around 10 3 CFU/L.…”
Section: Discussionmentioning
confidence: 99%
“…Although such water is not ingested, it can be aerosolized during the usage of sinks for handwashing, and it can create an exposure scenario to Legionella . LDT is rarely monitored for Legionella contamination [ 22 ] and, consequently, possible infection or illness risk has not yet been explored. To fill this gap of knowledge, the aims of this paper were: (i) to investigate Legionella contamination on LDT through the analysis of 6-year monitoring data from the faucet of toilet cabins and (ii) to develop a QMRA model for sink usage on LDT using monitoring data to understand the probability of Legionella infection in such exposure scenario.…”
Section: Introductionmentioning
confidence: 99%
“…The sampling method should be chosen depending on the purpose of sampling, such as post-outbreak investigation or preventive measurement. Sampling may be performed immediately after tap switching, or after at least one minute of water pre-flush, which is more representative for the characterisation of water quality in the system (Quaranta, 2012;Bedard, 2015).…”
Section: Discussionmentioning
confidence: 99%